KSZTAŁTOWANIE SIĘ MIESZANEGO SYSTEMU SZKOCKIEGO PRAWA PRYWATNEGO W XIX I XX WIEKU - Stępkowski, Aleksander (Zeszyty Prawnicze, 2017)
FORMATION OF THE MIXED SYSTEM OF SCOTTISH PRIVATE LAW DURING 19™AND 20™ CENTURIES (Summary) This paper présents development of Scots law as a mixed jurisdiction in 19th and 20th centuries. This spécifie mixture of légal cultures which is Scots law, owes most of its peculiarity to, variable in its character, relationships with England and its precedent based legal culture. English influence on Scottish private law become predominant in 19th century, as an effect of advancement of internal integration within United Kingdome. Scots law - as described in 18th century classical legal treaties - was in general based on continental ius commune, as presented in French and Roman-Dutch legal thought. Political and social consequences of the Union of 1707 allowed extremely intensive influence of English law in Scotland since second quarter of 19th century. This impact had miscellaneous character and was performed in a various ways. The easiest one was legislative activity of British Parliament, whose statutes in 19th century started to be progressively more and more important source of English law. Statutory influence was the easiest as the number of Scots in British Parliament never exceeded ten percent, so there was no problem in ignoring their objections, until the establishment of the Scottish Law Commission in 1965, which started to supervise legislation touching Scotland. Except statutory influence, considerable changes took place in the way of administering justice in Scodand. The most spectacular was decision of the House of Lords which in the beginning of 18th century had recognised its authority to revise judgements of the Court of Session – Scottish supreme court. In effect House of Lords started - regardless differences existing between Scots law and English law - to apply English rules in reviewing judgements of the Court of Session. Further influence of English rules into Scots law was provoked by the reform of the Court of Session, whose organisation and proceedings became considerably anglicised. It provoked that its decisions started to be regarded as a primary source of law by progressive acceptance of English stare decisis rule - which was not the part of Scottish legal system before. A kind of reaction for this process of Anglicisation was the interest of Scottish lawyers in studies of Roman law, as performed on continent in Netherlands and Germany. This interest subsequently was manifested in following ideas of German historical school. In consequence they started to underline the unique - domestic - character of Scots law, independent as well from English law as from continental tradition of civil law. The article is finishing with considerations upon possible consequences for Scots law of the process of devolution in Scodand which took place in 1998. It presents different opinions of Scottish lawyers, as to the future development of Scots law.